“Ticket to ride”: factors affecting park-and-ride travel in Perth, WA - Olaru, D.; Smith, B.; Xia, Jianhong (Cecilia); Chen, Chunmei; Lin, Ting; Ying, H.; Han, R. (Transport Research Society, 2014)
In many cities park-and-ride (PnR) is gaining popularity for its ability to integrate car drivingwith public transport. PnR increases access for residents living at the city’s edge and helpsalleviate congestion. In terms of efficiency PnR reduces investment on frequent publictransport services in low-density areas. PnR is particularly relevant to a low-density city like Perth, Western Australia. In recent years PnR has been a key ingredient to generating a high volume public transport ridership on newly constructed lines. More than 15,000 PnR bays have been incorporated into transitoriented developments (TOD) around the 20 stations. This in contrast to the 48 legacy stations which have in total 2,500 bays. The paper aims to identify the effectiveness of the PnR direction taken by Perth city planners by first looking at the differences in facilities at the older and newer stations. A survey of passengers’ stated importance of levels of service offered at rail stations is augmented by their ratings of the existing level of service. The attitudes and ratings of the PnR network are related to train patronage.